Analisis Strategi Digital Marketing Untuk Meningkatkan Penjualan Polis Asuransi Syariah - Herry (Ali Institute of Research and Publication, 2025)
This study examines how the implementation of Search Engine Optimization (SEO) can drive increased sales of sharia insurance policies at Prudential. The purpose of this study is to understand how SEO strategies can be used as an element of digital marketing to boost sales of sharia insurance policies offered by Prudential. The method used in this study is qualitative with a SWOT case analysis approach, to identify potential strengths, weaknesses, opportunities, and threats. The findings of the study indicate that a well-implemented SEO strategy can be a highly effective digital marketing tool for increasing sharia insurance sales. While there are challenges such as a lack of understanding of SEO and technical complexity, there are significant opportunities such as the increasing number of internet users and the growing demand for sharia insurance that can be utilized